Human papillomavirus infection-associated markers of the occurrence and progression of cervical intraepithelial neoplasias: from research developments to clinical practice - L. I. Korolenkova (Опухоли женской репродуктивной системы, 2014)
Cervical intraepithelial neoplasias (CIN), the stages of development in cancer of the cervix uteri (CCU) during persisting infections caused by human papillomavirus (HPV), are a disease frequently occurring in young women. The carcinogenic process lasts 3-5 to 10-30 years during which timely detection and organ-saving treatment for the lesion are possible. The development of markers for the persis- tence of HPV infection and the transition of a productive to transforming phase of infection (from mild to severe CIN) is a basis for the current approach to screening for CIN and BC and to a patient follow-up. The review paper presents the main areas of studies developing markers that are directly associated with HPV infection (HC2 viral load), virus typing, viral physical status, E6 and E7 mRNA, E2/E6 ratio) and its mediated action on host cells (p16INK4a, hTERT). The pathogenetic effect of HPV early genes and their association with the expression of basic surrogate markers are considered in detail. The majority of the presented markers are being actively put into clinical practice in foreign countries.